Clinical application of risk assessment in PAH: Expert center APRN recommendations. (22nd August 2022) - Wilson, Melisa; Keeley, Jennifer; Kingman, Martha; McDevitt, Susanne; Brewer, Jacqueline; Rogers, Frances; Hill, Wendy; Rideman, Zachary; Broderick, Meredith
Abstract: Performing longitudinal and consistent risk assessments for patients with pulmonary arterial hypertension (PAH) is important to help guide treatment decisions to achieve early on and maintain a low‐risk status and improve patient morbidity and mortality. Clinical gestalt or expert perception alone may over or underestimate a patient's risk status. Indeed, regular and continued use of validated risk assessment tools more accurately predict patients' survival. Effective PAH risk assessments are often underutilized even though many seasoned clinicians will attest to using these tools routinely. We present recommendations based on real‐world experience in varied clinical practice settings around the United States for overcoming barriers to facilitate regular, serial formal risk assessment. Expert advanced practice provider clinicians from mid to large‐size medical centers collaborated to formulate recommendations based on multiple discourses and discussions. Enlisting the help of support staff, such as medical assistants and nurses, to fill in available risk parameters in risk assessment tools can save time for providers and increase efficiency, as can technology‐based solutions such as integrating risk assessments into electronic medical records. Modified, abbreviated risk assessment tools can be applied to a patient's clinical scenario when all of a patient's data are not available to complete a more comprehensive assessment. Initial discussions regarding the overall meaning and prognostic importance of risk scores may assist patients to take on a more active role in terms of informed decision‐making regarding their care. A collaborative approach can help clinics establish consistent use of risk assessment.